CALCULATION ALGORITHM TRUSS UNDER CRANE BEAMS - N. K. Akaev1; A. K. Yusupov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Aim.The task of reducing the deflection and increase the rigidity of single-span beams are made. In the article the calculation algorithm for truss crane girders is determined.Methods. To identify the internal effort required for the selection of cross section elements the design uses the Green's function.Results. It was found that the simplest truss system reduces deflection and increases the strength of design. The upper crossbar is subjected not only to bending and shear and compression work due to tightening tension. Preliminary determination of the geometrical characteristics of the crane farms elements are offered to make a comparison with previous similar configuration of his farms, using a simple approximate calculation methods.Conclusion.The method of sequential movements (incrementally) the two bridge cranes along the length of the upper crossbar truss beams is suggested. We give the corresponding formulas and conditions of safety.